2011
DOI: 10.1029/2010jb007814
|View full text |Cite
|
Sign up to set email alerts
|

Toward understanding slip inversion uncertainty and artifacts: 2. Singular value analysis

Abstract: Seismic slip inversion is studied by means of singular value decomposition (SVD), with emphasis on the role of singular vectors and regularization of the solution. Because the stable part of the slip inversion result is given in terms of a linear combination of the leading singular vectors (representing directions in the model space most sensitive to data), the performance of the inversion depends simply on how well the real slip model can be expanded into these vectors. The analysis is demonstrated using a sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 17 publications
4
37
0
Order By: Relevance
“…Detailed presentations of the role of the SVD in understanding the properties of linear-inverse problems can be found in textbooks on geophysical inverse problems (Menke, 2012), or, for example, Olson and Apsel (1982) and Gallovič and Zahradník (2011) in the context of the slip inversions. The SVD approach implicitly assumes as the objective function the L2 norm of data residuals relative to model predictions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Detailed presentations of the role of the SVD in understanding the properties of linear-inverse problems can be found in textbooks on geophysical inverse problems (Menke, 2012), or, for example, Olson and Apsel (1982) and Gallovič and Zahradník (2011) in the context of the slip inversions. The SVD approach implicitly assumes as the objective function the L2 norm of data residuals relative to model predictions.…”
Section: Methodsmentioning
confidence: 99%
“…in which K is the index of the smallest singular value larger than λ c (Jackson, 1972;Wiggins, 1972;Gallovič and Zahradník, 2011). After truncating both the inverted and the target model, we evaluate the MVR using the following variant of equation (7), which we refer to as the truncated model variance reduction (TMVR): E Q -T A R G E T ; t e m p : i n t r a l i n k -; d f 9 ; 5 2 ; 7 2 1 TMVR 1 − jjm T −m T jj=jjm T jj:…”
Section: Comparison Metricmentioning
confidence: 99%
See 1 more Smart Citation
“…In principle, the model discretization in time is similar to the classical multi-timewindow method introduced by Hartzell and Heaton (1983), but the implementations of that approach are typically limited to about 10 windows (Hartzell and Langer, 1993). Our unrestricted multi-time-window approach allows for time windows to cover the whole duration of the rupture, at all fault locations, unlike other multi-time-window approaches used (Olson and Anderson, 1988;Das and Kostrov, 1990;Gallovič et al, 2009;Gallovič and Zahradník, 2011). Our approach does assume a known fault geometry, as typical in inversions (Hartzell and Heaton, 1983;Olson and Anderson, 1988;Graves and Wald, 2001;Ji et al, 2002).…”
Section: Model Parameterizationmentioning
confidence: 99%
“…Saraò et al (1998) found that stations on the hanging wall facilitate source inversion on dip-slip faults. The case of single-station inversion was considered in Gallovič and Zahradník (2011) to understand the individual contribution of each station. The present study is the first to consider systematically the effect of network spacing in regular 2D networks, including dense networks with a large number of stations that were prohibitively expensive for earlier studies and for certain inversion methods.…”
Section: Introductionmentioning
confidence: 99%